Pengaruh Rasio Likuiditas, Solvabilitas, dan Aktivitas Terhadap Profitabilitas Pada PDAM - Ali, Firman; Hasan, Hamida; Machmud, Mulyana (Fakultas Bisnis Institut Ilmu Sosial dan Bisnis Andi Sapada, 2022)
The purpose of this study is to examine the effect of the liquidity ratio as measured by the current ratio (CR), the solvency ratio as measured by the debt to asset ratio (DAR), the activity ratio measured by total asset turnover (TATO) on profitability which is measured. With return on assets (ROA). The research method used is descriptive quantitative. The population in this study is the Financial Report at PDAM In Indonesia for the last five years (2016-2020) which consists of a Balance Sheet and Profit and Loss Report. This research uses multiple linear regression analysis methods, which are processed with the help of the SPSS V23 program. This study's results indicate that the calculations from multiple linear regression that have been carried out are Y= 178.926 + 2.1185 X1 + 1.888 X2 + (-0.757 X3) + e. If liquidity, solvency, and activity are worth 0, then profitability is worth 178,926. The results of the t-test indicate that liquidity has no partial effect on profitability by seeing a significant 0.389 > 0.05 and a tcount value of 1.428 < ttable 12.706. While solvency does not affect profitability, it can be seen by the significance of 0.485 > 0.05 and the value of tcount 1.049 < ttable 12.706. And activity shows a positive but insignificant effect on profitability as indicated by looking at 0.086 > 0.05 and tcount 17.391 > t table 12.706, so training influences profitability. In addition, liquidity, solvency, and activity simultaneously affect profitability by looking at Fcount of 38.274 and Ftable of 19.16. While the results of the Adjusted R square or coefficient of determination of 0.965 mean that 96.5% of the dependent variable is influenced by the independent variable, while other variables outside the research model influence the remaining 3.5%.